2013
DOI: 10.1039/c3sc50239b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient one-pot ligation and desulfurization

Abstract: The combination of native chemical ligation and desulfurization is considered a powerful strategy in protein synthesis. Homogeneous desulfurization conditions based on a radical induced reaction have been widely used in the syntheses of various challenging proteins and their analogues. However, the presence of aryl thiols in the reaction mixture as a ligation catalyst hampers one-pot ligation/ desulfurization, hence mandating additional purification/lyophilization steps prior to desulfurization. This significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
85
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 30 publications
1
85
0
2
Order By: Relevance
“…[7] Further expansion of the native chemical ligation-desulfurization concept has been made possible through synthetic amino acids that bear side-chain thiol groups, which can facilitate ligation reactions in a similar manner to a Cys residue when incorporated at the N-terminus of peptide fragments. These amino acids can be efficiently desulfurized to afford the native residue following the ligation event (Scheme 1).…”
mentioning
confidence: 99%
“…[7] Further expansion of the native chemical ligation-desulfurization concept has been made possible through synthetic amino acids that bear side-chain thiol groups, which can facilitate ligation reactions in a similar manner to a Cys residue when incorporated at the N-terminus of peptide fragments. These amino acids can be efficiently desulfurized to afford the native residue following the ligation event (Scheme 1).…”
mentioning
confidence: 99%
“…The prevalence of this byproduct was dramatically reduced when ligation-deselenization reactions were performed as a one-pot protocol in the presence of exogenous MPAA. Under these conditions, the rate of deselenization also dramatically decreased, perhaps because of the ability of aryl thiols such as MPAA to act as competitive radical scavengers [126,127,144]. Nonetheless, native peptide products, including those bearing unprotected, non-ligation site Cys residues, were isolated in good yields following the one-pot protocol for ligation-deselenization at β-selenophenylalanine [149].…”
Section: Ligation-deselenization Chemistrymentioning
confidence: 96%
“…Interestingly, for the construction of the target protein, the authors also reported the use of a novel thiol additive, trifluoroethanethiol (TFET) 124, which facilitates the facile application of a one-pot ligation-desulfurization protocol [124]. Previous attempts to streamline the ligation-desulfurization strategy into a one-pot process have been hampered by the use of aryl thiol ligation additives which, because of their radical quenching ability [125], complicate the radical desulfurization process [126][127][128]. Given the importance of aryl thiol additives in modulating thioester reactivity and promoting rapid ligation reactions [15,16], a number of approaches have aimed to facilitate the post-ligation removal of aryl thiols.…”
Section: Aspartic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent desulfurization with free radical conditions and transformation of Cys to Ala in one pot afforded the desired Rev in 15% overall yield (Scheme 41). The Brik group [99] further demonstrated that a highly activated aryl thioester (MPAA) could proceed with NCL in the absence of additional aryl thiol, which would produce only 1 equiv. of aryl thiol and hardly influence the desulfurization step.…”
Section: One-pot Ligation-desulfurizationmentioning
confidence: 98%